Appearance Comparison, Appearance Self-Schema, Perfectionism, and Body Esteem Among Korean College Students ψ. (April 2019) - Ko, Stacy Y.; Wei, Meifen; Park, Hyun-joo; Wang, Kenneth
In this study, we examined whether the constructs of appearance self-schema and perfectionistic self-presentation were significant mediators for the direct association between physical appearance comparison and body esteem. A total of 290 South Korean students from a university in South Korea participated in this study. Results from structural equation modeling supported that both appearance self-schema and perfectionistic self-presentation were significant mediators for the relationship between physical appearance comparison and body esteem. A bootstrap method was used to assess the magnitude of the indirect effect, with 33% of the variance in body esteem accounted for by physical appearance comparison, appearance self-schema, and perfectionistic self-presentation. A multiple-group analysis showed that the mediation model could be applied equally to both men and women students in South Korea. The current study demonstrates how body esteem issues may unfold in a Korean cultural context where appearance is highly salient to one's identity.